Ali konzultacija radiologa z bolnikom lahko zmanjša število nepotrebnih radioloških preiskav? - Staparski Dobravec, Saša (Zdravniški vestnik, 2020)
Background: Clinical guidelines for managing non-specific back pain do not recommend X-ray imaging within 4-6 weeks from the onset of pain. The overstrain on radiology departments due to inappropriately indicated imaging prompted the introduction of consultations with radiologists. The new practice was started at the Community Health Centre Ljubljana (CHCL) in January 2013. Thus, the possibility of consultation is offered to all patients between 25 and 45 years of age, referred to spinal X-ray. Methods: Quantitative analysis included all spinal X-ray imagings performed at CHCL from 2011 to 2018. The data were compared with those of two other Slovenian outpatient radiological departments. Qualitative evaluation of consultation implementation was done with a survey, which was sent to all patients (N:497) who had undergone consultation, as well as to their referring physicians (N:134) in the beginning of 2016. Results: The number of referrals in CHCL is declining. The survey response rate was 48% for referral physicians and 30% for patients. The majority of physicians (95%) expressed an opinion that the postponing or resigning of imaging did not cause delay of diagnostic or therapeutic procedure. Most of them (95.9%) evaluated consultation as reasonable. Patients evaluated the acquired information as understandable (N=136; 97.1%), useful (N=113; 89.7%) and something new (N=91; 72.8%). Conclusion: Introduction of patients' consultations with a radiologist may reduce the number of non-indicated referrals. It is a simple, legitimate, professionally justified, harmless and cost-efficient service in radiology practice, which allows a direct personal transfer of medical experience and specific radiological expertise to the patient.
Keywords: bolečina v križu; low back pain; prevention; preventiva; rentgensko slikanje; x-ray scan